Energetic ion dynamics near Callisto. (February 2019) - Liuzzo, Lucas; Simon, Sven; Regoli, Leonardo
Abstract: We examine the dynamics of energetic magnetospheric ions in the highly perturbed and asymmetric electromagnetic environment of the Jovian moon Callisto. The Alfvénic interaction of the (nearly) corotating magnetospheric plasma with Callisto's ionosphere and induced dipole generates electromagnetic field perturbations near the moon, the structure of which vary as a function of Callisto's orbital position. For this study, these perturbations are obtained from the AIKEF hybrid model (kinetic ions, fluid electrons) which has already been successfully applied to Callisto's local plasma environment (Liuzzo et al., 2015, 2016, 2017). To isolate the influence of Callisto's ionosphere and induced dipole field on energetic ion dynamics, we analyze the trajectories of energetic hydrogen, oxygen, and sulfur ions exposed to various configurations of the locally perturbed electromagnetic fields. We present spatially resolved surface maps that display accessibility of Callisto to these ion populations for select energies from 1 keV to 5000 keV. The Alfvénic plasma interaction with (i) Callisto's induced magnetic field, (ii) Callisto's ionosphere, and (iii) the combination of both, all leave distinct imprints in these accessibility patterns. Draping of the magnetospheric field around Callisto's ionosphere partially shields the moon's trailing (ramside) hemisphere from energetic ion impacts, and the induced field tends to focus energetic ion impacts near Callisto's Jupiter-facing and Jupiter-averted apices. Depending on the nature of Callisto's Alfvénic plasma interaction, the accessibility of its surface to energetic protons may evolve non-monotonically with increasing energy. We also present maps of energetic ion accessibility and the resulting energy deposition onto Callisto at the time of the Galileo C3, C9, and C10 flybys. Our findings show that the shielding of Callisto's surface from energetic ion impacts is most effective during flybys that took place while the moon was located at an intermediate distance to the center of Jupiter's magnetospheric current sheet. In this case, the ionosphere and induced dipole field both make substantial contributions to the electromagnetic field perturbations near Callisto.